(untitled) (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Thematic interpretation (maudhu’i) is a pattern of interpretation by collecting verses of the Koran that have the same goal, meaning they both discuss one topic and arrange them based on the period of the verse down and pay attention to the background of the causes of the descent, then given explanation, description, comments, and points of content of the sentence. The purpose of this literature research is to find out thematic interpretations (maudhu’i) of the subject of the concept of student management in Islamic Education Institutions. In this study, the authors used a qualitative descriptive approach, and the type of research used was library research. The results of the literature review are: Based on the verses that have been described and analyzed, in the field of student management, the thematic interpretations are raised on QS. Al-Kahfi verses 23-24 and 69, QS Al-Hasyr verse 18, QS Az-Zumar verse 29, QS An-Nahl verse 125, and QS Al-Furqan verse 74, provide an explanation and explanation of the meaning of how student management is in perspective Al-Qur’an. Each of which is in the content as described above, namely that every activity to be carried out must be made with good planning, organization, and implementation and control, which in this case is especially in Surah Al-Kahfi verse 69 and Al-Furqan verse. 74 regarding guidance to students, so that students can develop their talents and interests as well as their competencies so that they become dzurriyah which are qurrota a’yun for parents and their second parents, namely the board of teachers in the Islamic educational institution.